Nurses’ information use and literature searching skills for evidence based practices - Shaheen, Majid; Foo, Schubert; Zhang, Xue; A Mokhtar, Intan; Luyt, Brendan; Chang, Yun-Ke; Theng, Yin-Leng; Majid, Shaheen; Foo, Schubert; Zhang, Xue; Mokhtar, Intan A; Luyt, Brendan; et al. (Malaysian Journal of Library and Information Science, 2017)
Majid, S., Foo, S., Zhang, X., Mokhtar, I. A., Luyt, B., Chang, Y. K., & Theng, Y. L. (2013). Nurses’ information use and literature searching skills for evidence based practices. Malaysian Journal of Library & Information Science, Vol.18, no. 1: 67-78. Medical and healthcare literature is growing exponentially, and medical professionals, including nurses, need to possess basic literature searching skills to retrieve information for clinical decision making. This study aims to investigate the use of different medical information sources by nurses and their literature searching skills. Questionnaire survey was adopted for data collection and a total of 1,486 nurses from two public hospitals in Singapore participated in this study. It was found that human and printed sources were used more frequently by the nurse, as compared to online sources. For literature searching, nurses used basic search features, and only less than one-quarter of them were familiar with Boolean and proximity operators. The study suggests that hospital libraries should play an active role in improving literature searching skills of nurses which may subsequently result in increased use of electronic information sources, where more updated clinical research information may be found.